Adherence to Antiretroviral Therapy in Conflict Areas: A Study among Patients Receiving Treatment from Lacor Hospital, Uganda - Garang, Piok G.; Odoi, Richard A.; Kalyango, Joan N. (AIDS patient care and STDs, 2009)
The interaction between limited resources, living in conflict areas, and complexity of HIV treatment may impact negatively on adherence to antiretroviral therapy (ART). Nonadherence may lead to development of resistant strains that may further increase the costs of management. The aim of this study was to compare the level of adherence to ART among internally displaced persons (IDPs) and non-IDPs and determine the factors associated with nonadherence. A cross-sectional study was conducted from January to February 2008 among adults receiving ART from Lacor Hospital. Systematic sampling was used to select 200 participants. Adherence was assessed through patients’ self-reports over a 4-day period. Data were collected using an intervieweradministered questionnaire and analyzed in SPSS version 12 (SPSS Inc, Chicago, IL). Patients were considered to be adherent if they took 95% or more of their medicines. Adherence rates among IDP and non-IDP patients were compared using Mann-Whitney U test. Factors associated with nonadherence were determined using logistic regression. The overall mean 4-day adherence was 99.5%. There was no significant difference in adherence between IDPs and non-IDPs (99.6% and 99.5%, respectively). Being on first-line regimen of ART (odds ratio [OR]¼22.22, 95% confidence interval [CI]¼1.48–333.33) and feeling that staff at the health centre were condemning (OR¼22.22, 1.53–333.33) were independently associated with nonadherence. Our study was limited in using only self-reports to assess adherence. In conclusion, patients in conflict areas can achieve high levels of adherence. Interventions to reduce nonadherence should address health provider–patient interaction and patients on first-line regimens.
Keywords: Adherence; Antiretroviral Therapy; Patients; Treatment; Lacor Hospital; Uganda